The Effect of Return on Asset and Return on Equity on Debt to Asset Ratio in PT. Medan Regional Office Life Insurance - Muslih Muslih; Muhammad Iqbal Novan (Journal of International Conference Proceedings (JICP), 2021)
The purpose of the study was to determine the effect of Return on Assets on the Debt to Asset Ratio, to determine the Return on Equity of the Debt to Asset Ratio, and to determine the effect of Return on Assets and Return on Equity on the Debt to Asset Ratio either partially or simultaneously at PT. Jiwasraya Insurance. The approach used in this study is an associative approach. Samples that meet the withdrawal criteria are carried out for ten years. Data collection techniques in this study using documentation techniques. The data analysis technique in this study uses the Classical Assumption Test, Multiple Regression, Hypothesis Testing (t-test and F-test), and the Coefficient of Determination. Data processing in this study using the SPSS version 22.00 software program. The results of this study prove that the Partial Return on Assets has an effect on the Debt to Asset Ratio, while the Return on Equity has an effect on the Debt to Asset Ratio. Simultaneously Return on Assets and Return on Equity affect the Debt to Asset Ratio.